School Enrichment Programmes to Bolster Self-Directed Language Learning Skills of Students' Limited English FAL Proficiency in Rural - Mokoena, Mosebetsi (Studies in Learning and Teaching, 2024)
Although English is the language of instruction in many South African schools, most learners are not native speakers of the language. As a result, attaining high levels of proficiency in English first additional language (English FAL) remains a problem for most learners in rural schools. Although many intervention strategies have been explored to address this challenge, research linking school enrichment programs, English proficiency, and self-directed learning in rural contexts remains limited. That is, little is known about how school enrichment programs could be used to bolster the self-directed learning skills of learners with limited English proficiency. Therefore, this qualitative study is guided by a transformative paradigm, the constructivist learning theory and participatory action research methodology to explore the use of school enrichment programs in bolstering learners’ self-directed language learning skills to improve proficiency in English FAL. For data generation, three teachers and nine learners of English FAL in one secondary school were conveniently selected to participate in the focus-group discussions and observations. A thematic analysis of data revealed that SEPs bolstered the self-directed language skills of learners by creating a space for remedial assistance in reading, providing a constructivist learning environment, and maintaining extrinsic motivation levels and supportive teacher-learner relationships.